The Student’s Speaking Ability of the Tenth Grade Gtudents of SMA 2 Genteng Through Picture Series - Zulaikah Zulaikah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
This study employed Collaborative Classroom Action Research design in which the researcher together with the classroom teacher. This classroom action research consisted of two cycles. The increasing can be seen from the changing of the students’ behavior in the teaching and learning process and from their score. The changing of behavior including activeness, dare, independent, and the reach of score increasing step by step. The increasing also shows in the students’ score before conducting the research and after conducting the research. The result of the speaking test in the first Cycle, the students’ percentage score was 41.0% the student can achieve the target score and in the second cycle, the students’ score was 88.00% who achieve the target score. It means that the result of the students’ speaking test improved in the second cycle and fulfilled the target of this research.